Biocatalytic synthesis and evaluation of antioxidant and antibacterial activities of hydroxyequols. (1st October 2022) - Nozawa, Daiki; Matsuyama, Akinobu; Furuya, Toshiki
Graphical abstract: Abstract: Hydroxyequols are promising analogues of the biologically active flavonoid, equol. We recently found that the flavin-dependent monooxygenase HpaBro-3 of Rhodococcus opacus regioselectively synthesizes 3′-hydroxyequol from equol, whereas HpaBpl-1 of Photorhabdus luminescens synthesizes 6-hydroxyequol. In this study, we investigated the cascade synthesis of a dihydroxyequol compound from equol using these two enzymes. When Escherichia coli cells expressing HpaBro-3 and cells expressing HpaBpl-1 were simultaneously incubated with equol, the cells efficiently synthesized 6, 3′-dihydroxyequol (8.7 mM, 2.4 g/L) via 3′- and 6-hydroxyequols in one pot. The antioxidant activity of the equol derivatives increased with an increase in the number of hydroxyl groups on the equol scaffold. 6, 3′-Dihydroxyequol exhibited potent antioxidant activity. In addition, 6-hydroxyequol significantly inhibited the growth of E. coli . Cell survival studies suggested that 6-hydroxyequol is a bactericidal rather than bacteriostatic compound. To our knowledge, this is the first report describing the antibacterial activity of hydroxyequols.